Design and Analysis of a Flutter-Based Mobile Application for Palm Oil Monitoring - Hannan, Ananda Rahmatul; Sopandi, Ajang; Firdaus, Ali; Kurniawan, Arif; Rusdianto, Hengki (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
In the current era of digital transformation, it is essential to modernize data processing systems to improve operational efficiency and competitiveness across industries. However, PT Agro Sawit Musi Rawas still relies on outdated manual processes, resulting in reporting delays, inaccurate data, and difficulties in real-time performance monitoring. Therefore, the aim of this research is to design a comprehensive monitoring system specifically tailored to meet the unique operational needs of PT Agro Sawit Musi Rawas. The system criteria were identified through methods such as observations, interviews, and literature reviews, which provided valuable insights into the company’s specific challenges and requirements. The system design incorporates data collection and analysis using the URS (User Requirement Specification) and UML (Unified Modeling Language) frameworks, ensuring it addresses the identified needs effectively. The design and analysis follow a structured and systematic process to develop an information monitoring system that enhances transparency, operational effectiveness, and efficiency. The findings reveal that the implementation of the proposed system can significantly improve reporting speed, data accuracy, and real-time monitoring capabilities. By adopting this monitoring system, PT Agro Sawit Musi Rawas can optimize reporting processes, facilitate real-time performance monitoring, and ultimately strengthen its competitive market position.